Governance networks in marine spaces where fisheries and oil coexist: Tabasco, México. Issue 2 (April 2020) - la Cruz, Carolina C Salazar-De; Alberto Zepeda-Domínguez, José; Espinoza-Tenorio, Alejandro; E Ramos-Muñoz, Dora
Highlights: ● Fifty-three stakeholders in eight groups form the fishing-oil SES in Mexico ● Three agendas in the governance network influencing fishing-oil SES ● The governance network in the coupled fishing-oil network has low cohesion ● The existence of different resources conditioned the participation of stakeholders ● The stakeholders' commitment influences the governance mechanism Abstract: Coupled Socio-Ecological Systems (SES) are frequent in the sea where several human activities coexist in a common space, maintaining individual attributes, but also creating inherent characteristics of this spatiotemporal coupling. The governance system, which minimises conflicts through maximizing agreements, offers an opportunity to achieve a balance between sectoral agendas. Establishing effective governance is challenging in the Southern Gulf of Mexico, where the new Energetic Reform (2013) has stressed the historically fragile equilibrium between fisheries and the oil industry. Through a Social Network Analysis (SNA), this work aims to identify the governance network directly involved in the decision-making process over the fishing-oil Socio-Ecological System (FOSES) of the coast of Tabasco. The mapping of 53 key actors (classified in eight functional groups) shows that the cohesion between them is low compared to the number of maximum relationships that could be established in the network. The distribution of the actors can be appreciated in three governance agendas. The energy agenda is ruled by the state oil company (PEMEX) and the Mexican Navy, while the social-fishing and intermediary environmental agendas are dominated by the fishing sector and the state environmental protection agency, respectively.